Relationships between highly skilled golfers` clubhead velocity and kinetic variables during a countermovement jump - Wells, J. E. T.; Mitchell, A. C. S.; Charalambous, L. H.; Fletcher, I. M. (Sports Biomechanics, 2022)
Previous research has sought to establish the relationship countermovement jump (CMJ) performance has with clubhead velocity (CHV). However, these investigations either assessed lower skilled golfers, or utilised field-based protocols, which are unable to assess a number of biomechanical variables. Fifty highly skilled golfers performed CMJs on Kistler force platforms in laboratory conditions. The CMJ variables included positive impulse, net impulse, average power, peak power, peak force, force at zero velocity and jump height. Clubhead velocity was measured using a TrackMan 3e launch monitor at a driving range. A Pearsons correlation was employed to measure the strength and direction of the relationships between CHV and CMJ derived performance variables. Results indicated strong positive relationships (all p`s <0.001) between CHV and positive impulse (r = 0.695), net impulse (r = 0.689), average power (r = 0.645), peak power (r = 0.656), peak force (r = 0.517) and force at zero velocity (r = 0.528) with no significant relationship with jump height. However, if investigators only have access to field-based protocols, it is recommended that they measure jump height and utilise inverse dynamics to calculate take-off velocity. By multiplying take-off velocity by mass, this allows the attainment of net impulse.